Methodological Options for Reading a Narrative of Collaboration Online in Canadian Education (Alberta Journal of Educational Research, 2020)
This study considers three methodological orientations for reading the narrative of collaboration taken root in contemporary discussions around publicly funded education in Canada. It looks through and beyond conflict theory and an archaeological historical approach and turns to a discursive method well suited to close analysis of recorded, text-based exchanges. Selecting discursive psychology and conversation analysis as preferred interpretive tools, it samples an exchange from an institutional interaction between a researcher, a teacher, and two parents in an online discussion forum. The analysis highlights the multiplicity of agendas and work generated across stakeholders by what is ostensibly one shared goal.Key words: minority parents, Canadian schools, online, discursive psychology, conversation analysisCette étude examine trois orientations méthodologiques pour interpréter le récit sur la collaboration qui s’est enraciné dans les discussions contemporaines portant sur l’éducation publique au Canada. L’étude part de la théorie des conflits et regarde au-delà de celle-ci, passe par une approche historique archéologique pour se tourner vers une méthode discursive bien adaptée à une analyse approfondie des échanges textes enregistrées.d Ayant privilégié la psychologie discursive et l’analyse des conversations comme outils d’interprétation, l’étude se penche sur un échantillon consistant en une interaction institutionnelle entre un chercheur, un enseignant et deux parents sur un forum de discussion en ligne. L’analyse fait ressortir la multiplicité de programmes et le travail généré par les parties prenantes vers ce qui est présenté comme étant un objectif partagé.Mots clés: parents minoritaires; écoles canadiennes; en ligne; psychologie discursive; analyse des conversations